Chemico-microstructural changes in earthen building materials containing calcium carbide residue and rice husk ash. (20th August 2019) - Nshimiyimana, Philbert; Messan, Adamah; Zhao, Zengfeng; Courard, Luc
Highlights: Curing process was monitored in mix solution made of earthen material-CCR-RHA based on EC and [Ca 2+ ]. Curing of mix solutions containing CCR alone reached the maturity of the reaction after 45 days. RHA accelerates the curing in mix solutions to reach the maturity of the reaction in 28 days. EC and [Ca 2+ ] could be useful to assess the reactivity of the materials in various curing conditions. Abstract: Clay earthen materials can essentially be stabilized with calcium carbide residue (CCR) and rice husk ash (RHA) to produce compressed earth block (CEBs) with improved mechanical performances for application in building construction. Nevertheless, the curing process in mixtures of these materials needs to be monitored in order to assess the maturation of the reaction among these materials and their reactivity. This study investigated the curing process in mix solutions and microstructural changes in the cured mixtures made of kaolinite-rich earthen material, portlandite-rich CCR, and silica (amorphous)-rich RHA. Dry mixtures were prepared by adding 0–25% CCR and 10–25% CCR:RHA (various ratios) to the earthen material (5 g). The mix solutions were prepared by addition of 100 mL of deionized water to the dry mixtures. Stabilized CEBs were also produced by manually compressing moisturized mixtures in 295 × 140 × 95 mm 3 mold. The curing process was undertaken between 1 and 90 days at 40 ± 2 °C. Throughout the curing, the chemical changes in mix solutions were monitored by measuring the pH, electrical conductivity (EC) and concentration of unconsumed calcium ions [Ca 2+ ]. The microstructural changes in cured mixtures were characterized using X-Ray diffraction (XRD), thermogravimetric analysis (TGA) and scanning electron microscopy (SEM). The EC and [Ca 2+ ] decreased over the curing time mainly due to the consumption of calcium ions through pozzolanic reaction involving the earthen material with CCR and CCR with RHA. The minimum values of EC and [Ca 2+ ] were reached after 45 days of curing in the mix solutions containing the earthen material and CCR alone and 28 days in those containing the earthen material and CCR:RHA. This was related to the end of the reaction and occurrence of optimum maturity in the respective mixtures. The XRD analyses revealed the consumption of kaolinite and portlandite from the raw materials and formation of calcium silicate hydrates (CSH) and calcium aluminate hydrates (CAH) in the cured mixtures. The SEM micrographs showed the formation of porridge-like products forming an interlocking network which densely cemented the matrix of stabilized CEBs.